A Novel Multicriteria Evaluation of Small-Scale LNG Supply Alternatives: The Case of Greece - Eleni Strantzali; Konstantinos Aravossis; Georgios A. Livanos; Nikos Chrysanthopoulos (Energies, 2018)
Natural gas as fuel for electricity production has significant advantages, such as the reduction of environmental emissions and the lower operational cost. Due to the flexibility of gas engines, the exploitation of renewable energy sources in an area, can be maximized. The main objective of the present study is to investigate the possibility of LNG supply for sustainable electricity production in insular small-scale electricity systems. A novel multicriteria evaluation model has been developed, based on the methods of Additive Value Model, PROMETHEE and Simos approach. A set of coherent criteria has been selected, that fits perfectly with the demands of this type of problem. The proposed methodology has been implemented in four Greek islands (as they are the most indicative examples and with future perspectives to use natural gas for electricity production) and in one power plant in the mainland (as another typical example of small-scale electricity production). The evaluation process included four supply alternatives that cover the annual fuel demands of the examined regions. The obtaining ranking showed that the development of a network supplying individual small-scale terminals in a roundtrip is preferable, compared to the separate supply of each terminal.